Experiment study of oscillating heat pipe and phase change materials coupled for thermal energy storage and thermal management. (August 2016) - Zhao, Jiateng; Rao, Zhonghao; Liu, Chenzhen; Li, Yimin
Highlights: Coupling oscillating heat pipe and phase change materials was proposed. The angle range with obviously affected thermal resistance decreases with the increase of heating power. Thermal response time of PCM was short, oscillation and temperature variation had good synchronization. The installation angle had minimal effect on the thermal performance of the coupling module. Abstract: In order to enhance the thermal performance of latent heat thermal energy storage (LHTES) system and thermal management system, a novel method that coupling oscillating heat pipe (OHP) and phase change materials (PCM) was proposed and investigated in this paper. The advantages of PCM and OHP could be combined to overcome each shortcoming. The expanded graphite (EG)/paraffin composite material and the closed loop OHP used in the experiment were prepared and tested. The thermal performance of the coupling module was studied experimentally under different operating conditions. The results showed that the angle range where thermal resistance is obviously affected by the installation angle decreases with the increase of heating power. The trend of the temperature difference between the closed loop OHP and EG/paraffin composite before the PCM melting was similar to those filled with water under the same condition, but the difference value was larger. The working condition of the OHP directly affects the thermal efficiency of the coupling system. The oscillation and the temperature variation have good synchronization. Relative to the EG/paraffin composite, it took about two times time for the paraffin to release heat from the same starting temperature to the ambient temperature.